2019
DOI: 10.1128/iai.00019-19
|View full text |Cite
|
Sign up to set email alerts
|

Control of Staphylococcus aureus Quorum Sensing by a Membrane-Embedded Peptidase

Abstract: Gram-positive bacteria process and release small peptides, or pheromones, that act as signals for the induction of adaptive traits, including those involved in pathogenesis. One class of small signaling pheromones is the cyclic autoinducing peptides (AIPs), which regulate expression of genes that orchestrate virulence and persistence in a range of microbes, including staphylococci, listeriae, clostridia, and enterococci. In a genetic screen for Staphylococcus aureus secreted virulence factors, we identified an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 96 publications
(150 reference statements)
3
41
0
Order By: Relevance
“…Many bacteria encode multiple CPBPs, with S. aureus NCTC8325 containing at least six other CPBP enzymes in addition to LnsB ( 62 ). Of these, MroQ is a suspected protease that processes auto-inducing peptide ( 63 , 64 ). There is phenotypic evidence for roles of four other staphylococcal CPBPs in maintaining cell envelope integrity ( 65 ) and in the expression of cell wall-attached surface proteins with YSIRK peptide signals ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many bacteria encode multiple CPBPs, with S. aureus NCTC8325 containing at least six other CPBP enzymes in addition to LnsB ( 62 ). Of these, MroQ is a suspected protease that processes auto-inducing peptide ( 63 , 64 ). There is phenotypic evidence for roles of four other staphylococcal CPBPs in maintaining cell envelope integrity ( 65 ) and in the expression of cell wall-attached surface proteins with YSIRK peptide signals ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Murine infection models. Murine skin and soft tissue and systemic infections were performed as previously described with WT, ΔlipL mutant, and ΔlipLϩlipL (ATG-1) mutant strains (3,62).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it has been suggested that LyrA interacts with the histidine kinases of 10 two-component systems of S. aureus, including WalK, which is involved in controlling cell wall metabolism, leading to the suggestion that LyrA is a global regulator of two-component system activity (18). Another S. aureus CAAX protease, MroQ, was reported to be a regulator of the Agr quorum sensing system, potentially via interaction with AgrC histidine kinase (27,28). The related CAAX protease homologue from group B streptococcus, Abx1, has been shown to interact with and regulate the two-component system CovRS (17).…”
Section: Discussionmentioning
confidence: 99%